Microwave ablation versus hepatic resection for the treatment of hepatocellular carcinoma and oesophageal variceal bleeding in cirrhotic patients. (3rd April 2017) - Zhang, Qiang-Bo; Zhang, Xiu-Guo; Jiang, Run-de; Hu, Chun-Xiao; Sun, Dong; Ran, Lin; Zhang, Zong-Li
Abstract: Purpose: The aim of this study was to compare the results of microwave ablation (MWA) and hepatic resection (HR) when combined with pericardial devascularisation plus splenectomy (PCDV) for the treatment of patients with cirrhosis complicated by small hepatocellular carcinoma (HCC) and oesophageal variceal bleeding (EVB). Materials and methods: Between 2001 and 2013, 73 patients (median age 53.2 years, 67% male) with small HCC and concomitant EVB who underwent MWA or HR for HCC and PCDV for cirrhotic portal hypertension were selected retrospectively for inclusion in this study. The overall survival curves and recurrence-free survival curves were calculated using the Kaplan–Meier method and compared using log-rank tests. Multivariate analysis was performed using the Cox regression model. Results: The 1-, 3- and 5-year overall survival rates were 95.2%, 71.4% and 38.1% and 96.7%, 53.3% and 43.3% for the HR and MWA groups, respectively; these did not differ significantly between the two groups. However, patients in the HR group had more post-operative complications (52.3% vs. 13.7%; p = 0.002). Multivariate analysis identified albumin and bilirubin levels and tumour size to be statistically significant and independent prognostic factors for overall survival, while BCLC stage was associated with poor recurrence-free survival. Furthermore, albumin levels were shown to be an independent predictive factor for post-operative complications. Conclusions: For patients with small HCC and concomitant EVB, MWA plus PCDV may reduce the incidence of post-operative complications relative to and provide similar therapeutic benefits as HR plus PCDV, especially for patients with low albumin levels.